2016
DOI: 10.1111/vop.12352
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional printing of orbital and peri‐orbital masses in three dogs and its potential applications in veterinary ophthalmology

Abstract: Three-dimensional printing in cases with orbital and peri-orbital masses has exceptional potential for improved surgical planning and provides another modality for visualization to help veterinarians, students, and owners understand distribution of disease. Additionally, as the techniques of 3D printing continue to evolve, the potential exists to revolutionize ocular surgery and drug delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…10,11 Also, in the near future, models created by three-dimensional printing of such images may further improve understanding of the topography of orbital lesions. 18 In the authors' opinion, the method presented here offers far superior exposure for tumor removal as compared to conventional exenteration techniques (Figures 3 and 4). Also, it greatly improves exposure over that of the previously published trans frontal orbitotomy 8 (Figure 7), especially as it offers simultaneous access to both the globe and the orbit (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…10,11 Also, in the near future, models created by three-dimensional printing of such images may further improve understanding of the topography of orbital lesions. 18 In the authors' opinion, the method presented here offers far superior exposure for tumor removal as compared to conventional exenteration techniques (Figures 3 and 4). Also, it greatly improves exposure over that of the previously published trans frontal orbitotomy 8 (Figure 7), especially as it offers simultaneous access to both the globe and the orbit (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 77%
“…The present authors have found contrast CT studies useful to determine the interrelationships of large vessels and orbital lesions . Also, in the near future, models created by three‐dimensional printing of such images may further improve understanding of the topography of orbital lesions …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the reference population drew not only from surveys of canine orbital tumors but from case series Unspecified adenocarcinoma or carcinoma (23) [3][4][5]8,9,[13][14][15][16]21,34 Lobular orbital adenoma (15) 27 Nasal adenocarcinoma (9) 6,13,41 Lacrimal gland adenocarcinoma (8) 6,12,[44][45][46][47] Squamous cell carcinoma (6) 6,[12][13][14]51,52 Nasal carcinoma (5) 12,14 Nictitans gland adenocarcinoma (4) 4,6,8,47 Zygomatic salivary adenocarcinoma (3) 4,69,70 Unspecified salivary adenocarcinoma (2) 8,13 Nictitans gland adenoma (2) 48,75 Ameloblastoma (2) 78,79 Zygomatic salivary adenoma (1) 81 Unspecified salivary adenoma (1) 12 Lacrimal gland adenoma (1) 84 Unspecified adenoma (1) 14 Iridociliary adenocar...…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional technology has been used in veterinary medicine in the manufacture of implants and prostheses 13 , in medical clinics 14 , for diagnosis 15 , for surgical planning 16 , for reproduction and for teaching. The latter includes studies of anatomy 17 , clinical 18 , diagnostic imaging 19 , and surgery 20 . Despite its use in several educational areas, studies in the area of veterinary anesthesiology have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%